Synthesis of cyclo-PLAI using a combination of solid- and solution-phase methods. Issue 2 (17th January 2019) - Napitupulu, Orin Inggriani; Sumiarsa, Dadan; Subroto, Toto; Nurlelasari,; Harneti, Desi; Supratman, Unang; Maharani, Rani
Abstract: Cyclo-PLAI was successfully synthesized using a combination of solid- and solution-phase methods. This current synthesis was found to be faster than the previously reported synthesis for the cyclic peptide. The linear precursor was synthesized on 2-chlorotrityl resin with Fmoc/ t -Bu strategy. HATU/HOAt was employed as the coupling reagent in the amide bond formation on the resin. Cyclization of the linear precursor was experimented with HATU/HOAt reagents with different conditions. However, the linear precursor was best cyclized using HATU reagent in DIPEA by stirring the reaction mixture at 0 °C for 1 h and followed by stirring the reaction mixture at room temperature for 30 min, giving the cyclic product in 70% yield (calculated from the linear peptide). Both linear and cyclic products were characterized using HR-TOF-ESMS, 1 H-NMR, 13 C-NMR, and compared with previously reported spectral data for the cyclic product. Graphical Abstract: